2013
DOI: 10.1186/1750-9378-8-41
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chlamydophila pneumoniae and human herpesvirus 8 in primary cutaneous anaplastic large-cell lymphoma: a case report

Abstract: BackgroundThe etiology of primary cutaneous anaplastic large-cell CD30+ lymphoma is largely unknown, and although an infectious involvement has been suspected, the implication of infectious agents in its pathogenesis is still unclear.FindingsWe report the case of a HIV-negative patient referred to our hospital with a rapidly enlarging skin tumor on her upper eyelid. Surgical excision was performed and histological analysis evidenced a primary cutaneous anaplastic large-cell lymphoma. Due to the ocular localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…Moreover, HHV8 infection causes a reprogramming of cell transcription, inducing the expression of cellular factors with proangiogenic activity, including VEGF, MCP-1, ATF4, mTOR, and ANGPTL4 [4,5,12,16,21,22]. In line with this, previous observations by our group evidenced a relevant presence of HHV8 in cutaneous vascular proliferative lesions, especially in eruptive cherry angiomas (CAs), and suggested that immunosuppression could be a substratum for HHV8 to explicate its neoangiogenic potential at skin level [1,2].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, HHV8 infection causes a reprogramming of cell transcription, inducing the expression of cellular factors with proangiogenic activity, including VEGF, MCP-1, ATF4, mTOR, and ANGPTL4 [4,5,12,16,21,22]. In line with this, previous observations by our group evidenced a relevant presence of HHV8 in cutaneous vascular proliferative lesions, especially in eruptive cherry angiomas (CAs), and suggested that immunosuppression could be a substratum for HHV8 to explicate its neoangiogenic potential at skin level [1,2].…”
Section: Introductionsupporting
confidence: 78%
“…The presence of HHV8 DNA in clinical biopsies was analyzed by three different molecular assays, as previously described [1,2,5,6]. Briefly, DNA was isolated from clinical samples and 100 ng of total DNA were analyzed by two qualitative PCRs (specific for ORF26 and ORF50 genes), and by a real time quantitative PCR (qPCR) (designed in the ORF26 gene, but amplifying a different region from that amplified in the qualitative PCR).…”
Section: Hhv8 Detectionmentioning
confidence: 99%
“…Specifically, genomic DNA sequences belonging to Ureaplasma spp and Mycoplasma spp were investigated using hemi-nested PCR (hn-PCR) and PCR, respectively (Cultrera, Seraceni, Germani, & Contini, 2006). The genomic DNA sequence of C. trachomatis was investigated by nested-PCR (Borghi et al, 2013). In PCR techniques, the following primers sets were used: (a) UU3/UU4 and UU5, targeting the urease gene of the most common human Ureaplasmas (Cultrera et al, 2006)…”
Section: Bacterial Dna Detectionmentioning
confidence: 99%
“…; (b) MGSO/ RNA5 and MGSO/GPO1 primer sets, targeting the 16S gene region of the most common human Mycoplasmas (a true positivity was considered if obtained with both pairs of primers; Cultrera et al, 2006); (c) and 16S generis, 16s-chtracho primer sets, targeting the 16S gene region of C. trachomatis(Borghi et al, 2013).…”
mentioning
confidence: 99%
“…However, the actual implication of infectious agents in the pathogenesis of such disorders remains controversial [ 1 5 ]. In a previous report [ 6 ], we reported the case of an immunocompetent female patient with a primary cutaneous CD30+ anaplastic large-cell lymphoma (PCALCL) of her upper right eyelid, characterized by the presence of a concurrent active infection by C. pneumoniae and Human herpesvirus 8 (HHV8). This finding suggested that these microorganisms could be involved in the development of the PCALCL by reciprocally potentiating their pathogenic potential.…”
Section: Introductionmentioning
confidence: 99%